2008
DOI: 10.1177/0886260508323663
|View full text |Cite
|
Sign up to set email alerts
|

Social and Emotional Outcomes of Child Sexual Abuse

Abstract: Childhood sexual abuse is a traumatic life event that may cause psychiatric disorders such as posttraumatic stress disorder and depression. During 2003-2004, 20 sexually abused children were referred to the Child and Adolescent Psychiatry Clinic of Ege University in Izmir, Turkey. Two years later, the psychological adjustment of these children (M age = 9.4 years, SD = 3.63 years, range = 5 to 16 years) is evaluated. Semistructured interviews, a form for the sociodemographic characteristics, are used for evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
1
18
2
5
Order By: Relevance
“…Psychological problems associated with CSA include depression, suicide, dissociation, posttraumatic symptomatology, anxiety, isolation, stigmatization, low selfesteem, and higher rates of both psychological and personality disorders (Miner, Flitter, & Robinson, 2006;Ozbaran et al, 2009;Polusny & Follette, 1995). Such psychological sequelae can lead to various behavioral problems including substance abuse (Kendler et al, 2000;Ullman, 2009), maladaptive and high-risk sexual behavior (Steel & Herlitz, 2005;Van Bruggen, 2006), eating disorders (Rayworth, Wise, & Harlow, 2004), suicidal behaviors (Filipas & Ullman, 2006;Plunkett et al, 2001), social dysfunction, interpersonal difficulties, sexual dissatisfaction, and lower quality of romantic relationships (Briere & Runtz, 1990;Messman-Moore & Long, 1996, 2003Polusny & Follette, 1995;Walker, Holman, & Busby, 2009).…”
mentioning
confidence: 99%
“…Psychological problems associated with CSA include depression, suicide, dissociation, posttraumatic symptomatology, anxiety, isolation, stigmatization, low selfesteem, and higher rates of both psychological and personality disorders (Miner, Flitter, & Robinson, 2006;Ozbaran et al, 2009;Polusny & Follette, 1995). Such psychological sequelae can lead to various behavioral problems including substance abuse (Kendler et al, 2000;Ullman, 2009), maladaptive and high-risk sexual behavior (Steel & Herlitz, 2005;Van Bruggen, 2006), eating disorders (Rayworth, Wise, & Harlow, 2004), suicidal behaviors (Filipas & Ullman, 2006;Plunkett et al, 2001), social dysfunction, interpersonal difficulties, sexual dissatisfaction, and lower quality of romantic relationships (Briere & Runtz, 1990;Messman-Moore & Long, 1996, 2003Polusny & Follette, 1995;Walker, Holman, & Busby, 2009).…”
mentioning
confidence: 99%
“…Although ignored in many developing countries, awareness has been rising in Turkey in recent decades, and research efforts have begun (i.e., Goregen & Tufekci, 2011;Karadag, Sonmez, & Dereobali, 2015;Koc, Halicioglu, & Aksit, 2014;Oral et al, 2001;Ozbaran et al, 2009). Descriptive analysis was applied to the results of this study; therefore, discussion points aim to provide a general profile of the findings rather than making specific inferences.…”
Section: Discussionmentioning
confidence: 98%
“…Psychopathology incidence was relatively lower in socially supported individuals who were also living in protective and functioning families. We had previously reported that the sexually abused children from divorced or separated family had a higher incidence of behavioral problems . In view of Bowlby's attachment theory, secure attachment is present in functioning and supportive families .…”
Section: Discussionmentioning
confidence: 99%
“…We had previously reported that the sexually abused children from divorced or separated family had a higher incidence of behavioral problems. 27 In view of Bowlby's attachment theory, secure attachment is present in functioning and supportive families. 28 Mickelson et al noted that parental divorce is negatively related to attachment security.…”
Section: Discussionmentioning
confidence: 99%